Perforated Appendicitis with Generalized Peritonitis in a Patient with Situs Inversus Totalis: A Case Report and Literature Review - Thomas Anggara (International Medical Journal Corp. Ltd, 2025)
INTRODUCTION: Situs inversus totalis (SIT) is a rare congenital condition characterized by the mirror-image transposition of thoracic and abdominal organs. Its co-occurrence with acute appendicitis, one of the most common surgical emergencies, presents a significant diagnostic challenge due to the atypical, left-sided clinical presentation. This can lead to diagnostic delays and an increased risk of complications. CASE ILLUSTRATION: A 40-year-old male presented to the emergency department with a three-day history of generalized abdominal pain that originated in the left lower quadrant (LLQ). Physical examination revealed tachycardia and signs of generalized peritonitis. Laboratory investigations showed marked leukocytosis. A chest radiograph incidentally revealed dextrocardia, raising suspicion for situs inversus. A subsequent abdominal ultrasound confirmed the transposition of visceral organs and identified findings suggestive of acute appendicitis in the LLQ. An emergency exploratory laparotomy was performed, which confirmed a perforated, gangrenous appendix located in the left iliac fossa, with approximately 200cc of purulent fluid in the peritoneal cavity. An appendectomy was performed, and the patient experienced an uneventful post-operative recovery. DISCUSSION: The patient's initial presentation with LLQ pain is a classic